The Relationship Between Responsiveness and Patient Satisfaction atPuskesmas Remaja - Noor Hariyani (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Responsiveness is a key dimension of healthcare quality, reflecting the extent to which services meet patient needs. Although responsiveness has been widely studied, evidence from Puskesmas Remaja settings remains limited, and gaps between patient expectations and service experiences are still reported. Objective : This study aimed to assess the level of service responsiveness at Puskesmas Remaja, examine patient satisfaction, and analyze the relationship between the two. Research Methods/ Implementation Methods : A cross-sectional survey was conducted with 755 respondents recruited through convenience sampling. Data were collected using a standardized electronic questionnaire, and bivariate analysis was performed using the Chi-Square test. Results : Of the total respondents, 306 rated service responsiveness as “Good” and 265 as “Very Good,” with corresponding satisfaction levels reported in similar categories. Statistical analysis confirmed a significant association between responsiveness and patient satisfaction (p < 0.001). Conclusion/Lesson Learned : Service responsiveness has a significant positive effect on patient satisfaction. Strengthening responsiveness should be prioritized as a strategic approach to improve service quality and patient experience in primary healthcare facilities.